The Profile of Oncologic Orthopedic Surgery in 2 Years of COVID-19 Pandemic: A Single-Centered Study in Orthopedic Hospital - Mujaddid Idulhaq; Fajar Baskoro Gardjito; Musa Fasa Roshada (Indonesian Journal of Cancer, 2023)
Background: COVID-19 pandemic has led to a difficult condition for healthcare providers to maintain their service without risking their safety. Generally, patients were canceling their hospital visits as they feared COVID-19 transmission. This has led to a general decline in the number of patient visits, attending doctors, and elective surgeries. However, this may not be the same for oncologic orthopedic cases which are allowed to continue elective surgeries, and the patients still perceive their condition as urgently in need of treatment. This article aimed to compare the number of oncologic orthopedic surgeries before and during the COVID-19 pandemic and describe the profile of oncologic orthopedic surgery two years of the pandemic.Methods: This was a retrospective study comparing the total number of oncologic orthopedic patients undergoing elective surgery in a single center, Prof. Dr. R. Soeharso Orthopedic Hospital, Surakarta, Indonesia, from March 2019 to February 2022. The number of surgeries per month before the pandemic, in the first and second years of the COVID-19 pandemic, was described and compared with one-way ANOVA. The surgical procedures performed in these three years were also described.Results: The total of oncologic orthopedic surgeries before the COVID-19 pandemic was 390 cases in comparison to 374 cases in the first year and 355 cases in the second year of the pandemic. The average number of cases per month was 32.5 ± 6.4 before the pandemic compared to 31.2 ± 7.8 in the first year and 29.5 ± 6.4 cases per month in the second year of the pandemic. There was no significant difference (p = 0.59, Confidence Interval 95%). Sophisticated reconstruction surgery such as arthroplasty and megaprosthesis still took place during the pandemic. Conclusions: The trend in the number of oncologic orthopedic surgeries did not decline significantly during the COVID-19 pandemic.